Vrednotenje sistemov, dostopnih prek spleta - Klemen, Aleš (Knjižnica, 2006)
An efficient online information service user interface enables independent use of these online. Designers of the GeaBios Internet information system intended to evaluate the user-friendliness of their service "Fast adresses" ("Hitri naslovi"). In December 2003, as a research project for a graduation thesis, an evaluation of "Fast adresses" was conducted. The study consisted of 10 study participants performing assigned tasks and a survey of the same individuals. During the study research questions were developed as well as list of tasks to be assigned to the participants for the observations. Each observation was performed using a qualitative research paradigm. This paradigm was enhanced with an adaptation of Shneiderman's (1998) questionnaire. Identified difficulties participants had in using "Fast adresses" fell into four types: (1) formulation of queries, (2) display of results, (3) the influence of the operating system, Windows and (4) the color and design of the display background and elements of the Web page. Results indicate that the difficulties encountered were not limited to the inappropriate design of the user interface, but also are attributable to user error.
Keywords: informacijski sistemi; uporabniški vmesniki; spletni informacijski sistemi; GeaBios; anketiranje; opazovanje; vrednotenje